Mass Fragmentation Characteristics of New Psychoactive Substances of Nitazenes - Qian-ya DENG; Jin-lun XU; Chun-fang NI; Fang-qi CAO; Yang SI; Si-yang HE; Shui-qing ZHENG; Chen LIANG (Zhipu Xuebao)
2-Benzylbenzimidazole opioids, also referred to “nitazenes”, has been noted with increasing frequency in the recreational drug market. These compounds were first synthesized in the 1950s, marking the pharmaceutical industry’s initial achievement of high-level morphine-like activity without relying on the complex phenanthrene moiety of poppy alkaloids. Although nitazenes exhibit strong analgesic properties and have been used in in vitro receptor study and in vivo addiction behavior research, they have never been approved for any pharmaceutical or clinical applications due to risks such as addiction and respiratory depression. Since 2019, nitazenes have seen a rapid surge in the illicit drug market, with underground laboratories synthesizing them as alternatives to opioids like fentanyl and heroin. The chemical structures of nitazenes have been swiftly modified to evade regulatory control, leading to the emergence of novel compounds. In order to investigate the mass fragmentation characteristics of nitazenes and encapsulate the analytical strategy of structural identification, ten mitazenes, including 2-(2-(4-ethoxybenzyl)-5-nitro-1H-benzo[d]imidazol-1-yl)-N,N-diethylethan-1-amine (etonitazene), 2-(2-(4-chlorobenzyl)-5-nitro-1H-benzo[d]imidazol-1-yl)-N,N-diethylethan-1-amine (clonitazene), and N,N-diethyl-2-(2-(4-isopropoxybenzyl)-5-nitro-1H-benzo[d]imidazol-1-yl)ethan-1-amine (isotonitazene), etc were analyzed using gas chromatography coupled with quadrupole/time of flight-mass spectrometry (GC/Q-TOF MS) and ultra-performance liquid chromatography coupled with quadrupole-Orbitrap mass spectrometry (UPLC-Q-Orbitrap MS). The mass fragmentation pathways of the studied compounds were examined under both electron ionization (EI) and electrospray ionization (ESI) with high-energy collisional dissociation (HCD) mode, they have both congruencies and distinctive features. Under EI mode, nitazenes predominantly undergo α-cleavage at the nitrogen-containing substituents at the 1st position, leading to the formation of an iminium cation, which is typically observed as the base peak in the mass spectra. While, under ESI-HCD mode, the cleavage of the C—N bond occurs at the 1st position, yielding a cation derived from the substituents, which manifests as the base peak with a mass increment of 14 u relative to the iminium cation observed under EI mode. The insights garnered from this study are anticipated to significantly enhance the structural elucidation of nitazenes, thereby contributing to the advancement of analytical methodologies in the field of forensic chemistry and drug analysis.